Analisis Kesulitan Menerjemahkan Teks Bahasa Arab Ke Bahasa Indonesia Kelas VII A MTs Ismaria Al Qur’aniyyah Rajabasa Bandar Lampung - Rahmah Yanah; M. Zaky Sya’bani; Kasmudi (Al Mitsali, 2022)
Translating in general is a process of transferring ideas or ideas from the source language to the target language. Translating activities are not only often associated with an urgent need to convey ideas or ideas from one language to another, but also related to efforts to learn and master a particular foreign language. This study aims to: 1) To determine students' ability to translate Arabic text into Indonesian for class VII A students of MTS Ismaria Al Quraniyyah Rajabasa Bandar Lampung. 2) To find out the teacher's efforts in overcoming difficulties translating Arabic texts into Indonesian for class VIII A MTs Ismaria Al Quraniyyah Rajabasa Bandar Lampung. This study uses a descriptive qualitative approach. In collecting data using observation techniques, interviews and documentation. While the data analysis technique used is data reduction, data presentation and conclusion. The results of this study were 1) The ability of class VII A students at MTs Ismaria Al Qur'aniyyah in translating Arabic texts was still low, because it was seen from the answers to the questions translating Arabic texts that no student achieved the KKM standard score. 2) The teacher's efforts in overcoming difficulties in translating, the teacher evaluates the Arabic lessons that have been studied, the teacher always gives good examples in learning Arabic, the teacher teaches looking for vocabulary in the dictionary, the teacher uses fun methods, the teacher helps students translate by demonstrating movements, and the teacher reminds and motivates students.